Enhancement of the heat transfer in radiator with louvered fin by using Graphene-based hybrid nanofluids. Issue 1 (February 2021) - Sandhya, M; Ramasamy, D; Sudhakar, K; Kadirgama, K; Harun, W S W
Abstract: Newly developed hybrid nanofluids can enhance heat transfer performance of various automotive appliances. Improved thermophysical properties of this hybrid nanoparticles when used as coolants will enhance the effectiveness of the car radiators with improved engine cooling system. The present study involves the simulation-based analysis of thermal enhancement of Graphene based Hybrid Nanofluids in a Car radiator. System analysis is performed considering single tube component in the radiator for pattern development. CFD analysis is conducted using ANSYS FLUENT module. Graphene/Crystal Nanocellulose hybrid (Graphene + CNC) nanoparticles are suspended in water & ethylene glycol base fluids (40:60) at 0.01%, 0.05%, 0.1% &0.2 % volume concentration considering at 3-7 LPM inlet mass flow rate. The effect of various volume concentration, inlet temperature and flow rate on Pressure, Enthalpy, Entropy, Heat transfer coefficient, and Heat transfer rate has been examined by simulation. The results indicate that when using a Louvered fin in a radiator, Maximum enhancement of 60% in heat transfer rate, 53% increase of heat transfer coefficient, 65% increase in pressure are achieved for Graphene with CNC hybrid nanofluids when compared with Graphene based nanofluids. Using this type of hybrid coolants along with louvered fin in radiator can significantly improve the heat transfer performance of radiators.